Effect of gear ratio on peak power and time to peak power in BMX cyclists - Rylands, L. P.; Roberts, S. J.; Hurst, H. T. (European Journal of Sport Science, 2017)
The aim of this study was to ascertain if gear ratio selection would have an effect on peak power and time to peak power production in elite Bicycle Motocross (BMX) cyclists. Eight male elite BMX riders volunteered for the study. Each rider performed three, 10-s maximal sprints on an Olympic standard indoor BMX track. The riders` bicycles were fitted with a portable SRM power meter. Each rider performed the three sprints using gear ratios of 41/16, 43/16 and 45/16 tooth. The results from the 41/16 and 45/16 gear ratios were compared to the current standard 43/16 gear ratio. Statistically, significant differences were found between the gear ratios for peak power (F(2,14) = 6.448; p = .010) and peak torque (F(2,14) = 4.777; p = .026), but no significant difference was found for time to peak power (F(2,14) = 0.200; p = .821). When comparing gear ratios, the results showed a 45/16 gear ratio elicited the highest peak power,1658 ± 221 W, compared to 1436 ± 129 W and 1380 ± 56 W, for the 43/16 and 41/16 ratios, respectively. The time to peak power showed a 41/16 tooth gear ratio attained peak power in -0.01 s and a 45/16 in 0.22 s compared to the 43/16. The findings of this study suggest that gear ratio choice has a significant effect on peak power production, though time to peak power output is not significantly affected. Therefore, selecting a higher gear ratio results in riders attaining higher power outputs without reducing their start time.